The Role of the Sabhara Unit of the Magelang Police Patrol Unit in the Prevention of Motorized Vehicle Theft - Bonifasius Lagowan (Advances in Police Science Research Journal, 2020)
This research is motivated by the rampant theft of motor vehicles in Magelang Police Station. The efforts made by the Sabhara Unit have not yet resolved the problem due to the continuing crime rate. Thus, the most effective effort is to conduct a review of the Sabhara Unit Patrol Unit. Therefore, a study was carried out aimed at finding out the ability of Sabhara Patrol Unit personnel, the methods used in preventing motorized vehicle theft, the intensity of Patrol implementation based on the quality and quantity approaches and the factors causing the occurrence of curanmor. This research was conducted with a qualitative approach, using descriptive analysis research methods, as well as data collection techniques by interviewing, observing, and studying documents. The results of the study found that the activities of the Patrol in order to reduce the number of fraud and prevent the emergence of opportunities and intentions for the perpetrators of criminal acts were seen to be not optimal. Analysis of the ability of officers with the concept of motor vehicle theft as well as the theory of the role and theory of crime prevention shows the optimal ability of officers by fulfilling some of the existing assessment indicators of each concept and theory. There are several factors that influence, factors that support other factors that support the function and optimize the performance of the Sabhara Unit in crime prevention, while the inhibiting factors are human resource factors, budget factors, facilities and infrastructure factors, as well as community trust in the police that are less and individuals who are not aware of the dangers around.